2022
DOI: 10.1002/anie.202208037
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Coordination Assembly of Dynamic Metal‐Phenolic Networks

Abstract: Coordination states of metal-organic materials are known to dictate their physicochemical properties and applications in various fields. However, understanding and controlling coordination sites in metal-organic systems is challenging. Herein, we report the synthesis of site-selective coordinated metal-phenolic networks (MPNs) using flavonoids as coordination modulators. The site-selective coordination was systematically investigated experimentally and computationally using ligands with one, two, and multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…The Raman spectra of MPN and Au-MPN ( Figure 1 E) show the characteristic Raman bands at 1350 and 1480 cm −1 , ascribing to the skeletal vibrations of the benzene ring [ 20 ]. In addition, the chemical composition of Au-MPN shows the common features of its precursors, as confirmed by the FT-IR spectra ( Figure 1 F), such as 1645 cm −1 (C=O stretching), 1440 cm −1 (C–O stretching), 1282 cm −1 (C–N stretching), 1192 cm −1 (O–H bending), and 1060 cm −1 (C–OH stretching) [ 26 , 38 , 39 ]. We also observe a reduced intensity of the C–OH band in the spectral lines of MPN and Au-MPN compared with that of TA, indicating the coordination of the phenolic groups with Fe ions [ 21 ].…”
Section: Resultsmentioning
confidence: 67%
“…The Raman spectra of MPN and Au-MPN ( Figure 1 E) show the characteristic Raman bands at 1350 and 1480 cm −1 , ascribing to the skeletal vibrations of the benzene ring [ 20 ]. In addition, the chemical composition of Au-MPN shows the common features of its precursors, as confirmed by the FT-IR spectra ( Figure 1 F), such as 1645 cm −1 (C=O stretching), 1440 cm −1 (C–O stretching), 1282 cm −1 (C–N stretching), 1192 cm −1 (O–H bending), and 1060 cm −1 (C–OH stretching) [ 26 , 38 , 39 ]. We also observe a reduced intensity of the C–OH band in the spectral lines of MPN and Au-MPN compared with that of TA, indicating the coordination of the phenolic groups with Fe ions [ 21 ].…”
Section: Resultsmentioning
confidence: 67%
“…[11] The binding energy of Fe II to β-Glu was predicted to be G B * = 38.6 kJ mol À 1 , which is not high but comparable to that of Fe II to QUE (particularly at the catechol sites, G B * = 26.9 kJ mol À 1 ) at pH 4 (Figure S10). [12] The predicted energy exchange for Fe II transfer from the catechol site of QUE to β-Glu was + 11.7 kJ mol À 1 (Figure S10b), which equals the ratio of Fe II -QUE and Fe II -Glu complexes of 114 : 1 at equilibrium under equimolar conditions (Figure 2b). The concentration of Glu is significantly higher than the effective concentration of QUE (> 200 : 1), which would nearly completely counteract this underlying energetic preference for QUE complexation, leading to the exchange of QUE and Glu and the re-conformation of metal-organic networks.…”
Section: Resultsmentioning
confidence: 96%
“…Specifically, Δ G s of Fe II binding to various sites of α‐Glu and β‐Glu with different deprotonated states (i.e., fully, single, or doubly deprotonated) were first systematically calculated (Figures S7–S9), thus identifying the most energy favorable Fe II −Glu complexes (Figure 2a). [11] The binding energy of Fe II to β‐Glu was predicted to be G B *=38.6 kJ mol −1 , which is not high but comparable to that of Fe II to QUE (particularly at the catechol sites, G B *=26.9 kJ mol −1 ) at pH 4 (Figure S10) [12] . The predicted energy exchange for Fe II transfer from the catechol site of QUE to β‐Glu was +11.7 kJ mol −1 (Figure S10b), which equals the ratio of Fe II ‐QUE and Fe II ‐Glu complexes of 114 : 1 at equilibrium under equimolar conditions (Figure 2b).…”
Section: Resultsmentioning
confidence: 97%
“…1a). 25,26 The complex formation of LUT and Fe 3+ was first characterized by UV-Vis spectroscopy. The UV-Vis spectrum of non-chelated LUT in a water/ethanol mixture (1/20 v/v) characteristic p-p* absorbance bands at 250 nm and 350 nm, corresponding to the benzoyl and cinnamoyl bands, respectively (Fig.…”
mentioning
confidence: 99%
“…In detail, the LMCT of LUT-Fe 3+ species showed the bands at 480 nm for the catechol tris-complex, and 560 nm for the catechol bis-complex. 26,28 We found that the simple vortexing of a biphasic system (LUT in oil and Fe 3+ in water) formed LUT-Fe 3+ shells on polystyrene (PS) microparticles (diameter: 3.97 mm), in which a 1 : 1 (v/v) combination of LUT (5 mM; in 1-octanol) and Fe 3+ (5 mM; in water) was used. The formation of LUT-Fe 3+ species was confirmed by the naked eye, as the particle suspension changed from white to dark green in color (Fig.…”
mentioning
confidence: 99%